Comprehensive analysis of molecular characteristics between primary and breast-derived metastatic ovarian cancer - Long J; Liu B; Li J; Ji X; Zhu N; Zhuang X; Wang H; Li L; Chen Y; Li X; Zhao S (AME Publishing Company, 2025)
Background: The molecular basis for the disparities between primary ovarian cancer (POC) and ovarian cancer secondary to breast cancer (OCSTBC) remains poorly understood. This study aimed to explore the different characteristics between them through genomic analysis. Methods: We performed differentially expressed genes (DEGs) analysis between POC (n=96) and OCSTBC (n=44) groups with transcriptome data and revealed the enriched biological pathways with Kyoto Encyclopedia of Genes and Genomes (KEGG) and Hallmark gene sets between these two groups. Then, the Microenvironment Cell Populations (MCP)-counter and Cell-type Identification by Estimating Relative Subsets of RNA Transcript (CIBERSORT) algorithms were applied to evaluate the immune infiltration in tumor microenvironment (TME) between them. Finally, we performed the association analysis within single nucleotide polymorphism (SNP) data and obtained some meaningful SNPs and candidate genes for further transcriptomic analysis. Results: We identified a total of 13 cancer-related genes including GATA3, FOXA1, CCND1, and TTK between POC (n=96) and OCSTBC (n=44) groups with DEGs analysis. Integrated analysis revealed more significant immune-enriched pathways in the POC than in the OCSTBC group. Most immune cells had higher infiltration abundance in POC, except M2 macrophages, which was higher in OCSTBC. In SNP analysis, four SNP regions (8q12.1, 11q21, 11q24.3, and 17q25.3) were found to be significantly correlated with phenotypes (POC/OCSTBC), and importantly, some new susceptibility genes such as ETS1, CWC15, and XKR4 were revealed to potentially be associated with distinction between POC and OCSTBC. Conclusions: Our study provides a systematic molecular characteristic between POC and OCSTBC and suggests a pressing need to develop some specific therapeutic strategies in certain types of ovarian cancer.
Keywords: Breast cancer; metastasis; primary ovarian cancer (POC); genes